Analisis Dampak Kesulitan Belajar Terhadap Perkembangan Akademik Peserta Didik SDIT Hajjah Fauziah Kota Binjai: Studi Fenomenologi - Rini Rahma Safitri; Isnaini Sapitri Br. Purba; Lili Raflika; Abdul Fattah Nasution (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
Learning obstacles are a major concern in education due to their impact on students’ academic achievement and overall development. This research seeks to explore how learning difficulties influence academic progress among elementary students. Using a qualitative phenomenological method, the study investigated the lived experiences of two fifth-grade students from SDIT Hajjah Fauziah in Binjai, gathering data through in-depth interviews and document analysis. The results revealed four prominent effects: (1) consistent and widespread academic decline, particularly in interconnected subjects; (2) a drop in learning motivation leading to disengagement and passive behavior; (3) cumulative knowledge gaps that worsen over time due to incomplete understanding; and (4) long-term implications on higher education, career opportunities, and students' emotional well-being. These findings underscore the necessity of implementing adaptive teaching methods and providing psychological support to address learning barriers early on